RANCANG BANGUN SISTEM PERSEDIAAN KAPAS BERBASIS WEB DI PT. ARGO MANUNGGAL TRIASTA - Irfan, Muhamad (University of Muhammadiyah Tangerang, 2021)
— Design a web-based cotton Inventory System at PT. Argo manunggal TriastaPT. Argo Manunggal Triasta is an industrial company engaged in the field of Textile. This company is one of the many companies in Indonesia that has obstacles in the delivery of information, especially information data about reports in and out of goods, reports of final stock of goods and all problems related to inventory. This makes the data management process slow, as does the provision of information when needed so that it hinders the process ofselling / releasing goods. By designing a better system, it is expected to be able to assist and facilitate the ongoing system processes in managing data, including processing, compiling, and storing data which ultimately produces accurate data that can be used for company needs. The results of the analysis are described using the UML (Unified Modeling Language) modeling language. Implementation inthe form of the final results achieved is the formation of a web-based information system that can facilitate users in managing data.— Design a web-based cotton Inventory System at PT. Argo manunggal TriastaPT. Argo Manunggal Triasta is an industrial company engaged in the field of Textile. This company is one of the many companies in Indonesia that has obstacles in the delivery of information, especially information data about reports in and out of goods, reports of final stock of goods and all problems related to inventory. This makes the data management process slow, as does the provision of information when needed so that it hinders the process of selling / releasing goods. By designing a better system, it is expected to be able to assist and facilitate the ongoing system processes in managing data, including processing, compiling, and storing data which ultimately produces accurate data that can be used for company needs. The results of the analysis are described using the UML (Unified Modeling Language) modeling language. Implementation in the form of the final results achieved is the formation of a web-based information system that can facilitate users in managing data.